In-depth insight into the photocatalytic and electrocatalytic mechanisms of Mg3V2O8@Zn3V2O8@ZnO ternary heterostructure toward linezolid: Experimental and DFT studies. Issue 1 (February 2023) - Mirsadeghi, Somayeh; Ghoreishian, Seyed Majid; Zandavar, Hamed; Behjatmanesh-Ardakani, Reza; Naghian, Ebrahim; Ghoreishian, Maryamsadat; Mehrani, Azadeh; Abdolhoseinpoor, Nargers; Ganjali, Mohammad Reza; Huh, Yun Suk; Pourmortazavi, Seied Mahdi
Abstract: Heterogeneous catalysis has been extensively studied as a potential means of overcoming the challenges associated with the detection and elimination of pharmaceutical pollutants in wastewater. In the present study, a novel ternary Mg3 V2 O8 @Zn3 V2 O8 @ZnO (MVO@ZVO@ZnO) composite catalyst was synthesized in three steps using a hydrothermal approach for the first time. The catalytic performance of the composite was investigated for the photodegradation of linezolid (LIZ) under visible light. The LIZ degradation rate of MVO@ZVO@ZnO (the photocatalyst with the optimal composition) was ∼12, 6.5, 7.8, and 2.6 times higher than those of ZnO, ZVO, MVO, and ZVO@ZnO, respectively. This significantly higher photocatalytic efficiency was attributed to synergism between its constituents, a narrow bandgap, improved light-harvesting ability, and greater charge-carriers separation and migration. Reactive-radical trappi ng experiments demonstrated that hydroxyl and superoxide radicals were largely responsible for LIZ degradation. Assisted by the ultraviolet photoelectron spectroscopy analyses and density functional theory calculations, the charge-carriers pathway and corresponding photocatalytic mechanism were thoroughly discussed in double S-scheme system. Furthermore, the MVO@ZVO@ZnO composite was used as an electrocatalyst to detect small amounts of LIZ in an aqueous medium and exhibited a detection limit of ∼0.33 μM. We believe that our findings encourage efforts to develop vanadate-based photocatalysts for use in environmental decontamination and detection applications. Graphical Abstract: ga1 Highlights: MVO@ZVO@ZnO composite catalyst was synthesized by hydrothermal method to detect and remove linezolid. The OH and O2− radicals played a more significant role in the successful removal of linezolid. DFT predicted intermediate species and degradation pathway over composite photocatalyst. Double S-scheme photocatalytic mechanism was proposed to explain the activity enhancement. Ultra-low detection limit and high sensitivity were obtained for the sensing of linezolid.